Research on Influence of Equivalent Conicity on Lateral Stability of 120 km/h Metro Vehicles - Hao LI; Huanyun DAI; Qunsheng WANG; Shenyu PENG; Jie WANG (机车电传动)
Based on the fact that 120 km/h B-type metro vehicles had a large wheel equivalent conicity in actual operation, a multi-body dynamic model of the vehicle was established with Simpack dynamic simulation software, which could restore the abnormal vibration after wheel wear in actual operation. Simulation results showed that when the equivalent conicity of the vehicle was 0.5, the vehicle body had 5.5 Hz vibration frequency caused by bogie hunting and 2.5 Hz vibration frequency caused by the track irregularity excitation of the upper center roll mode of the vehicle body, which resulted into large lateral stability index of the vehicle body. Through the analysis of suspension parameters, it was found that increasing the primary lateral positioning stiffness properly could effectively reduce the vehicle lateral stability index when the equivalent conicity was larger.